Formation of economically-effective model of tax gas producing enterprises in the Russian Federation; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Balandina A. S. Anna Sergeevna (2016, 2016)
Title screen